Managing menstruation with dignity: Worries, stress and mental health in two water-scarce urban communities in India - Neetu Choudhary; Cindi SturtzSreetharan; Sarah Trainer; Alexandra Brewis; Amber Wutich; Kathryn Clancy; Urooba Ahmed Fatima; Mohammad Jobayer Hossain (Taylor & Francis Group, 2023)
An emerging body of literature examines multiple connections between water insecurity and mental health, with particular focus on women's vulnerabilities. Women can display greatly elevated emotional distress with increased household water insecurity, because it's them who are primarily responsible for managing household water and uniquely interact with wider water environments. Here we test an extension of this proposition, identifying how notions of dignity and other gendered norms related to managing menstruation might complicate and amplify this vulnerability. Our analysis is based on systematic coding for themes in detailed semi-structured interviews conducted with twenty reproductive-age women living in two water insecure communities in New Delhi, India in 2021. The following themes, emerging from our analysis, unfold the pathways through which women's dignity and mental health is implicated by inadequate water: ideals of womanhood and cleanliness; personal dignity during menstruation; hierarchy of needs and menstruation management amidst water scarcity; loss of dignity and the humiliation; expressed stress, frustration and anger. These pathways are amplified by women's expected roles as household water managers. This creates a confluence of gendered negative emotions - frustration and anger - which in turn helps to explain the connection of living with water insecurity to women's relatively worse mental health.